The Effect of Digital Marketing, E-Commerce, and Entrepreneurship Education (As Moderating Variables) on the Interest in Entrepreneurship Among Students of State Vocational Schools in Malinau Regency - Rahmad Hari Setiyono; Mahendra Adhi Nugroho (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study analyzes the influence of Digital Marketing, E-Commerce, and Entrepreneurship Education on the entrepreneurial interest of vocational high school students in Malinau Regency and the moderating role of Entrepreneurship Education. The research method used a quantitative ex post facto approach with PLS-SEM analysis through SmartPLS 4.0 on 261 respondents in grade XII. The results show that Digital Marketing has a positive and significant effect on Entrepreneurial Interest, while E-Commerce has a positive but insignificant effect. Entrepreneurship Education has the strongest and most significant effect on Entrepreneurial Interest. Entrepreneurship Education negatively moderates the relationship of Digital Marketing, but positively and significantly strengthens the effect of E-Commerce on Entrepreneurial Interest. These findings emphasize the importance of practice-based entrepreneurship education and the integration of digital skills in enhancing students' entrepreneurial interest in the digital era.